(untitled) (Eurasian Research Bulletin, 2023)
The article discusses experience education development of the Republic Uzbekistan, implementation of different education forms, reveals the recent trends and its analysis has been given. The urgent need to improve the existing educational process management system under new conditions has been stressed, with a special focus on using the financial independence granted recently to the republic’s universities